Bimbingan Kesulitan Belajar Berbasis Self Regulating Learning dalam Meningkatkan Prestasi Belajar Siswa - - Sunawan; Dwi Yuwono Puji Sugiharto; Catharina Tri Anni (Universitas Negeri Malang, 2013)
Abstract: Self-regulated Learning as a Learning Guidance Model to Improve Learning Achievement. This study aims at developing a guidance model to deal with students' learning problems and examining the effectiveness of its implementation. The development of self-regulated learning as the learning model involved senior high school students, advisory teachers, subject-matter teachers, and the headmaster. This learning model is geared toward encouraging the students to utilize self-regulated learning. This model appeared to be able to improve the students' learning achievement. Abstrak: Bimbingan Kesulitan Belajar Berbasis Self Regulating Learning dalam Meningkatkan Prestasi Belajar Siswa. Penelitian ini bertujuan untuk mengembangkan dan menguji efektivitas model bimbingan kesulitan belajar bagi siswa SMA berbasis self regulated learning. Desain penelitian pengembangan digunakan untuk pengembangan model dengan melibatkan subjek dari siswa SMA, guru pembimbing, guru bidang studi dan kepala sekolah. Model bimbingan belajar berbasis self regulated learning diarahkan untuk mendorong siswa untuk menerapkan prinsip self regulated learning dalam belajarnya. Terbukti bahwa model ini dapat meningkatkan pola belajar siswa selaras dengan prinsip self regulated learning dan prestasi belajar.